Research Institute of Internal and Preventive Medicine, Branch, Federal Research Center, Institute of Cytology and Genetics, Siberian Branch, Russian Academy of Sciences - A. V. Titarenko; S. V. Shishkin; L. V. Shcherbakova; E. G. Verevkin; M. Holmes; M. Bobak; S. K. Malyutina (Неврология, нейропсихиатрия, психосоматика)
Age-related cognitive changes in the Russian population have not been sufficiently studied.Objective: to assess the time course of changes in cognitive functions (CF) in two serial measurements 9 years apart in the urban population of middle, elder, and senile age and their relationship to education level.Patients and methods. A random male and female sample of45-69-year-old Novosibirsk residents (n=9360; HAPIEE project) was surveyed. CF was tested by standard methods. Resurvey was conducted in a random subsample (n=1663) included in this analysis. The mean follow-up period was 8.8 years (SD 1.1).Results and discussion. The test for semantic verbal fluency revealed its dynamic decline in all age groups, which was steeper in women than in men (p<0.001). Persons aged 70 years and older showed negative changes in memory, verbal fluency, and attention (p<0.001). Persons with primary (6%) and vocational (26%) education had steeper rates of decline in delayed recall (p=0.011; 0.038) than those with university education (35%).Conclusion. It is established that a dynamic decrease in CF begins at the age of55—59years; it is steeper among those aged 70 years and older. An age-related decline in memory function is accelerated in persons with lower educational levels.